AN IMPLEMENTATION OF THE VALUE OF CHARACTER EDUCATION IN THE FORMING OF DISCIPLINE ATTITUDE IN CLASS V STUDENTS OF SDN DAYUHARJO SLEMAN - Heru Purnomo; Aprilia, Wida (Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas PGRI Yogyakarta, 2022)
ABSTRAK This study aims to determine how the implementation of character education values ​​in the formation of discipline in fifth grade students of SDN Dayuharjo Sleman. The type of research used is qualitative research with descriptive methods. The subjects in this study were the fifth grade students of SD Negeri Dayuharjo Sleman, totaling 45 people and the key informants in this study were homeroom teachers, subject teachers and school principals, determining the subject using a purposive method. Data collection techniques using interview and observation methods. Data analysis techniques used are data collecting, data reduction, data display and data classification. The results showed that; the implementation of the value of character education in the formation of discipline in class V SDN Dayuharjo Sleman has not been implemented optimally. Indicators of student indiscipline are arriving late to school, students going in and out of the classroom during class hours. Efforts that can be made to overcome obstacles in the process of implementing character education, especially in shaping students' disciplined attitudes, are through habituation of behavior carried out by students in class, by exemplary students in class in obeying any existing regulations. Keywords: Character Education, Discipline, Student.